Wakeful rest during storage and consolidation enhances priming effects for those with acquired memory impairment. Issue 4 (21st April 2021) - Riley, Gerard A.; Pearce, Arthur
ABSTRACT: A period of rest after learning results in better explicit memory for the material than a period of unrelated mental activity. This study investigated whether the same applies to priming. Thirty-four people with memory impairments due to acquired brain injury took part. In a repeated measures design, participants studied word lists; then either engaged in a relaxation technique (wakeful rest condition) or completed visuo-spatial tasks (control condition); and finally completed two priming tasks. Priming effects were significantly larger in the wakeful rest condition. This result is difficult to explain in terms of some of the explanations used to account for the benefits of wakeful rest on explicit memory, and alternative explanations are considered. One possibility is that the attentional demands of the control task resulted in inhibition of activity in neocortical areas associated with perception that contributed to the priming effect. The findings have implications for memory rehabilitation. Acquired memory impairments typically impact on explicit memory, and implicit memory is often relatively intact. It is important to find ways of enabling those with more severe explicit impairments to make best use of their implicit memory as a way of compensating for the deficits in their explicit memory.